RESENTRALISASI URUSAN PEMERINTAHAN ANTARA PEMERINTAH DAN PEMERINTAH DAERAH DALAM SISTEM KETATANEGARAAN INDONESIA (STUDI TERHADAP PASAL 10 AYAT 5 HURUF A UNDANG-UNDANG NOMOR 32 TAHUN 2004) - R. SONDANG TINAMBUNAN, SH A21208031, Jurnal Mahasiswa S2 UNTAN (Jurnal NESTOR Magister Hukum, 2013)
ABSTRACTThis thesis focuses on the recentralization of government affairs between the Government and Local Government in the constitutional system of Indonesia ( the study of article 10 , paragraph 5, letter a of Law No. 32 of 2004 . Outcome of the authors of a study using normative legal research methods , it is concluded ; Inside article 10 paragraph ( 5 ) letter a of Law No. 32 of 2004 which states